Financial development and economic growth:a panel data approach - Leitão, Nuno Carlos (2010)
The relationship between financial development and economic growth has been studied long time in economics (Adam Smith and Schumpeter). Structural reforms and the integration of financial markets have been attracting the interest of the academic community. This manuscript examines the link between financial development and economic growth. The European Union Countries (EU-27), and BRIC (Brazil, Russia, India and China) were examined, between 1980 and 2006. Using a static and dynamic panel data approach, the results demonstrate that the financial development contribute to economic growth. Our study also consider productivity and trade, these proxies confirm the positive effect on economic growth.